Áreas Protegidas, un contenido de superación necesario para los maestros de la Educación Primaria (Original) (Revista científico-educativa da província de Granma, 2024)
From theoretical and bibliographic foundations, the need of a research, already designed, is exposed. It starts from the insufficiencies presented by Primary School teachers regarding the knowledge on the attention to protected areas and the theoretical inconsistencies determined in the epistemological study. It is demonstrated the importance of these as a context and content for teachers training, in correspondence with the demands of the social-historical context. As a solution to this problem, a methodology based on a method and a system of procedures will be provided.